A legal study on enticement and section 498 of the penal code in Malaysia / Noor Farahin Ibrahim, Qatrin Nada Harun, Rabiatol Adariah Nordin - Ibrahim, Noor Farahin; Harun, Qatrin Nada; Nordin, Rabiatol Adariah (2010)
The recent case of Daphne Iking in 2009 had brought Section 498 of the Penal Code on the law on enticement, to light. Before this case, not many were aware of the existence of such a law in Malaysia since it is seldom invoked. A debate has arisen on whether Section 498 is still a valid and applicable law. Some had viewed it as an archaic and unequal law that is inconsistent with the Federal Constitution. While others had supported the existence of Section 498 since it is deemed that such a law contribute towards protecting the family institution. Thus, this research is done with the view of finding out the relevancy and validity of Section 498 under the Federal Constitution.